Development of Spectrophotometric methods for Assay of Salbutamol in Pharmaceutical Formulations - Theiaa N. Al-Sabha (College of Education for Pure Sciences, 2007)
Abstract Two sensitive spectrophotometric methods are proposed for the determination of salbutamol in pure form and pharmaceutical preparations. The methods are based on the oxidation of salbutamol drug with Fe(III) in acidic medium. The liberated Fe(II) reacts with 1,10-phenanthroline in method A and the ferroin complex is colorimetrically measured at 510 nm against reagent blank. Method B is based on the reaction of the liberated Fe(II) with 2,2'-bipyridyl to form a stable coloured complex with maximum absorption at 520 nm against reagent blank. Beer's law was obeyed in the concentration range of 0.15-6.00 µg/ml and 0.25-8.00µg/ml with molar absorptivity of 7.858×104 and 4.555×104 l.mol-1.cm-1 for method A and B respectively. The mean percent recoveries are 100.39% and 99.11% for both methods respectively. The suggested procedures could be used for the determination of salbutamol in pure and dosage forms without interference from common excipients. The proposed methods are successfully compared with the official and other spectrophotometric methods.